Neither Cytochrome P450 Family Genes nor Neuroendocrine Factors could Independently Predict the SSRIs Treatment in the Chinese Han Population - Zhang, X.; Yu, T.; Li, X.; Li, X.; Huang, X.; Li, X.; He, L.; He, G.; Sun, X. (Pharmacopsychiatry, 2014)
This study was intended to explore the relationship between the genetic polymorphisms of the 8 single nucleotide polymorphisms (SNPs) at CYP genes, neuroendocrine factors and the response to selective serotonin reuptake inhibitors (SSRIs) in Chinese Han depressive patients.This was a 6-week randomized controlled trial consisting of 290 Chinese Han depressive patients treated with SSRIs. 8 SNPs of CYP450 genes and 7 neuroendocrine factors were detected. Allele and genotype frequencies were compared between responders and non-responders. The relationships between neuroendocrine factors and treatment response were also analyzed.No significant differences were found in clinical features between 2 groups at the baseline. No statistical correlation was found between either the genotype or allele frequencies of SNPs in CYP1A2, CYP2C19, or CYP2D6 gene and the efficacy of SSRIs. There were strong linkage disequilibria between rs4986894, rs1853205, and rs12767583 of CYP2C19 genes, and rs2472299, rs2472300 of CYP1A2 genes. No associations were found between the above haplotypes and the antidepressant response. No neuroendocrine factor was a significant predictor for a response to SSRI antidepressants independently. The combination of neuroendocrine factors, however, predicted the response by 76.1%.There were no significant associations between the 6 SNPs of CYP gene polymorphisms and SSRI response. Neither cytochrome P450 family genes nor neuroendocrine factors independently predict the patients’ response to the antidepressants separately. A combination of neuroendocrine factors, however, does have the potential to predict the response.
Keywords: major depressive disorder; CYP2D6; CYP2C19; CYP2C9; CYP1A2; pharmacogenetics; neuroendocrine factors